New records and invasive potential of the poeciliid fish Phalloceros caudimaculatus - J. J. L. Rowley; T. S. Rayner; G. H. Pyke (New Zealand Journal of Marine and Freshwater Research, 2005)
Many species from the family Poeciliidae have been transported around the world by the aquarium trade, often establishing populations in areas far outside their natural range. The one‐spot livebearer, Phalloceros caudimaculatus is one such poeciliid species. In March 2002, a nonindigenous population of P. caudimaculatus was discovered at Collaroy, in the Sydney metropolitan area, the first record of this species in eastern Australia. Following this discovery, electrofishing and light‐trap surveys were conducted at the site, and dip‐netting and visual surveys were conducted in surrounding water bodies. P. caudimaculatus was widespread and abundant at the Collaroy site, but no further populations were discovered. Another pest poeciliid species, Gambusia holbrooki, originally present at the site, was absent and, although the mechanism remains unclear, may have been displaced by P. caudimaculatus. Both P. caudimaculatus and G. holbrooki share the characteristics of successful invasive species, with extremely broad physical tolerances and high reproductive outputs. Given the well‐documented negative ecological effects of poeciliids, especially G. holbrooki, we recommend that a precautionary approach should be adopted for the management of P. caudimaculatus and its eradication from the site be attempted.